Forward Roll Ability of PJKR FIKK UNM Students - Ikadarny (Journal Physical Health Recreation (JPHR), 2025)
This study aimed to analyze the forward roll ability of Physical Education, Health, and Recreation students at the Faculty of Public Health, Universitas Negeri Malang (FIKK UNM). The forward roll is a basic floor gymnastics skill and a prerequisite for mastering complex movements. The research method used was a descriptive quantitative survey. The sample consisted of 40 Physical Education, Health, and Recreation students, and data was collected through a structured assessment rubric covering the initial stance, execution, and final stance. The results showed that 4 students (10%) were in the very good category and 5 students (12.5%) were in the good category. However, the majority of the sample fell into the "fair" to "very poor" category, with 17 students (42.5%) in the fair category, 13 students (32.5%) in the poor category, and 1 student (2.5%) in the very poor category. Overall, the forward roll ability of the Physical Education, Health, and Recreation students at FIKK UNM was in the fair category. This is evident from the average scores obtained and the data distribution, which indicates that although some students had good mastery, the majority still experienced difficulties, particularly in the execution and final stance aspects of the movement.